2022
DOI: 10.3390/ijms23158119
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Relationships in Temperature Effects on Bacterial Luciferases: Nothing Is Perfect

Abstract: The evaluation of temperature effects on the structure and function of enzymes is necessary to understand the mechanisms underlying their adaptation to a constantly changing environment. In the current study, we investigated the influence of temperature variation on the activity, structural dynamics, thermal inactivation and denaturation of Photobacterium leiognathi and Vibrio harveyi luciferases belonging to different subfamilies, as well as the role of sucrose in maintaining the enzymes functioning and stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Enzymes from two subfamilies (such as Vibrio harveyi and Photobacterium leiognathi ) differ slightly in the architecture of the active site gorge and in the mode of substrate binding, as well as in the composition of the functional mobile loop. Our previous research showed that they are also characterized by distinct dynamic properties [ 26 , 27 ]. Therefore, in the present study, the homology-modeled structure of P. leiognathi luciferase was used instead of the resolved crystal structure of V. harveyi luciferase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Enzymes from two subfamilies (such as Vibrio harveyi and Photobacterium leiognathi ) differ slightly in the architecture of the active site gorge and in the mode of substrate binding, as well as in the composition of the functional mobile loop. Our previous research showed that they are also characterized by distinct dynamic properties [ 26 , 27 ]. Therefore, in the present study, the homology-modeled structure of P. leiognathi luciferase was used instead of the resolved crystal structure of V. harveyi luciferase.…”
Section: Resultsmentioning
confidence: 99%
“…The all-atom molecular dynamics (MD) of bacterial luciferase surrounded by water and cosolvents was simulated using GROMACS 2020.04 with CHARMM36 force field [ 50 , 51 ]. In order to model specific interactions of P. leiognathi luciferase surface and functional loops with cosolvents, its initial coordinates were obtained via homology-based modeling as described in [ 27 ]. Luciferase was modeled without any of the reaction components and their derivatives, since their structures in complex with the enzyme have not been crystalized yet (except for the product of the reaction [ 52 ]), and conformational changes in the protein were the focus of this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation